Complications of use locked intramedullary nail in the treatment of fractures of femur - Almeida, Maxsuel Fidelis de Pádua; Farias, Thales Carneiro; Lisboa, João Bruno Ribeiro Machado (Revista de Medicina, 2012)
The femoral shaft fractures are frequent and often serious accidents result from high-energy, which can affect other organs. Nowadays many orthopedists and traumatologists prefer therapeutic option for intramedullary rods, which is an example of fixation, which present a procedure with a simple surgical technique, standardized, contributes to better stabilize the fracture with minimal manipulation of the fragments order to maintain its vascularization, reduced damage to soft tissues and the potential for consolidation be greater, thus allowing an early load. But this is not free of complications, and postoperative infection the most feared. Objective: To analyze the scientific publications about the complications that most affect patients undergoing this surgical technique. Methodology: Literature review through a literature search. located through the Virtual Health Library (VHL) Result: A total of 16 scientific papers and observed a total of 326 patients. Where we found 215 complications, these complications anisomelia has a higher incidence (50.70%), fails to consolidate follows with (17.21%), soft tissue infection (6.98%), limited arc of motion knee (5.58%); rotational deviation (4.65%), angular deviation (4.19%), insertion of the rod in the bursa (2.33%), fat embolism (1.86%) and pneumonia ( 1.40%), pain (0.93%)., wound infection (0.93%). and pulmonary embolism (0.93%), osteomyelitis (0.47%), epiphyseal necrosis (0.47%), DVT (0.47%), respiratory failure (0.47%) and perforation of the cortex of the femoral neck (0.47%). Conclusion: We found very few complications with this technique in not considering any other factors that will unleash it. In future research were to be analyzed if these values are related to the technique performed, or the reduction of risk factors for the surgical procedure.